Deciphering the multifaceted roles and clinical implications of 2-hydroxyglutarate in cancer - Jie Hao; Ziyi Huang; Siyue Zhang; Kefan Song; Juncheng Wang; Chao Gao; Zhiqing Fang; Ning Zhang (Elsevier, 2024)
Increasing evidence indicates that 2-hydroxyglutarate (2HG) is an oncometabolite that drives tumour formation and progression. Due to mutations in isocitrate dehydrogenase (IDH) and the dysregulation of other enzymes, 2HG accumulates significantly in tumour cells. Due to its structural similarity to α-ketoglutarate (αKG), accumulated 2HG leads to the competitive inhibition of αKG-dependent dioxygenases (αKGDs), such as KDMs, TETs, and EGLNs. This inhibition results in epigenetic alterations in both tumour cells and the tumour microenvironment. This review comprehensively discusses the metabolic pathways of 2HG and the subsequent pathways influenced by elevated 2HG levels. We will delve into the molecular mechanisms by which 2HG exerts its oncogenic effects, particularly focusing on epigenetic modifications. This review will also explore the various methods available for the detection of 2HG, emphasising both current techniques and emerging technologies. Furthermore, 2HG shows promise as a biomarker for clinical diagnosis and treatment. By integrating these perspectives, this review aims to provide a comprehensive overview of the current understanding of 2HG in cancer biology, highlight the importance of ongoing research, and discuss future directions for translating these findings into clinical applications.